2012
DOI: 10.1124/dmd.111.044008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of P-Glycoprotein Leads to Improved Oral Bioavailability of Compound K, an Anticancer Metabolite of Red Ginseng Extract Produced by Gut Microflora

Abstract: ABSTRACT:Ginsenosides are hydrolyzed extensively by gut microflora after oral administration, and their metabolites are pharmacologically active against lung cancer cells. In this study, we measured the metabolism of various ginsenosides by gut microflora and determined the mechanisms responsible for the observed pharmacokinetic behaviors of its active metabolite, Compound K (C-K). The results showed that biotransformation into C-K is the major metabolic pathway of ginsenosides after the oral administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 35 publications
4
53
1
Order By: Relevance
“…For example, in a study, a P-gp blocker was able to increase paclitaxel concentration in blood (Kang et al, 2001). In addition, Compound K, the major component obtained from ginsenosides metabolism which is being used in treatment of lung cancer, showed reduced plasma C max and AUC 0-24h when P-gp was inhibited (Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study, a P-gp blocker was able to increase paclitaxel concentration in blood (Kang et al, 2001). In addition, Compound K, the major component obtained from ginsenosides metabolism which is being used in treatment of lung cancer, showed reduced plasma C max and AUC 0-24h when P-gp was inhibited (Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study, a P-gp blocker was able to increase paclitaxel concentration in blood (Kang et al, 2001). In addition, Compound K, the major component obtained from ginsenosides metabolism which is being used in treatment of lung cancer, showed reduced plasma C max and AUC 0-24h when P-gp was inhibited (Yang et al, 2012).On the other hand, some studies refused the role of P-gp in drug efflux. For example, in an experiment performed by Dickens et al, hypothesis claiming that P-gp is overexpressed at the epileptic focus was rejected as antiepileptic drugs like carbamazepine and lamotrigine were proven not to be substrate for P-gp (Dickens et al, 2013).…”
mentioning
confidence: 99%
“…In previous studies, diabetes downregulated intestinal P-gp function and Rh2 and C-K were identified as the substrate of P-gp (Liu et al, 2009;Yang et al, 2011Yang et al, , 2012; however, these findings were controversial, implying that increased Rb1 absorption may be associated with downregulation of intestinal P-gp Transport of FD4 (1 mg/ml) and FLU (0.1 mg/mL) from the apical to basal (A→B) direction was measured to evaluate the permeability of the Caco-2 monolayer cultured with 10% rat serum. (D) Rb1 (10 mM) transport across the Caco-2 monolayer cultured with 10% rat serum from both the A→B and B→A direction.…”
Section: Discussionmentioning
confidence: 97%
“…The experiment protocol and calculation were described in our previous reports (58). Briefly, an HBSS containing the compound(s) of interest was loaded onto the apical or basolateral (donor) side.…”
Section: /[I])mentioning
confidence: 99%
“…The uptake of tested compounds was determined according to our previous protocol (58). Briefly, after the transport study, the cell membranes were rinsed three times with ice-cold HBSS, pH 7.4.…”
Section: /[I])mentioning
confidence: 99%